Contributing Factors to Performance of Islamic Mutual Funds - Hasniyanti Hassan, Hafinaz; Hussin, Nazimah (International Journal of Psychosocial Rehabilitation, 2020)
Global Islamic mutual funds industry has developed impressively during the past three decades. In Malaysia, although Islamic mutual fund exist during 1970s, their existence has not had muchinfluence on the industry. Malaysia’s Islamic mutual fund industry started to grow rapidly during 1990s. Various studies have assessed the Islamic mutual fund performance throughout the world. Nevertheless, in Malaysia, there are dearth analysis on the factors influencing the performance of Islamic mutual fund. Therefore, the objective of this study is to ascertain the factors that influence Islamic mutual fund performance. The study is significant as it applies Theory of Performance in the Islamic mutual fund context. This study will offer further insights not only to the fund management companies but also to the potential investors on the factors that influence the performance of mutual fund.